Guidelines for the use of magnetic resonance imaging in diagnosing and monitoring the treatment of multiple sclerosis: recommendations of the Swedish Multiple Sclerosis Association and the Swedish Neuroradiological Society. (24th August 2016) - Vågberg, M.; Axelsson, M.; Birgander, R.; Burman, J.; Cananau, C.; Forslin, Y.; Granberg, T.; Gunnarsson, M.; von Heijne, A.; Jönsson, L.; Karrenbauer, V. D.; Larsson, E.‐M.; et al.
Abstract : Multiple sclerosis (MS) is associated with inflammatory lesions in the brain and spinal cord. The detection of such inflammatory lesions using magnetic resonance imaging (MRI) is important in the consideration of the diagnosis and differential diagnoses of MS, as well as in the monitoring of disease activity and predicting treatment efficacy. Although there is strong evidence supporting the use of MRI for both the diagnosis and monitoring of disease activity, there is a lack of evidence regarding which MRI protocols to use, the frequency of examinations, and in what clinical situations to consider MRI examination. A national workshop to discuss these issues was held in Stockholm, Sweden, in August 2015, which resulted in a Swedish consensus statement regarding the use of MRI in the care of individuals with MS. The aim of this consensus statement is to provide practical advice for the use of MRI in this setting. The recommendations are based on a review of relevant literature and the clinical experience of workshop attendees. It is our hope that these recommendations will benefit individuals with MS and guide healthcare professionals responsible for their care.